FETTERING OF PRESIDENTIAL DISCRETION: DID THE PUBLIC PROTECTOR OVERREACH? - Molefhi S Phorego; Hendrik J van As (Obiter, 2023)
The President’s power to establish a commission of inquiry confers a plethora of discretionary powers for the Head of State. In the exercise of this power, the President acts alone, seemingly without the constitutional obligation to consult any public functionary or institution. This creates challenges for the question of accountability that attends the exercise of the power. Following the release of the State Capture Report, the Public Protector found that the President had inter alia outsourced his power to appoint cabinet members to the Gupta family, notwithstanding that he was the only one empowered to exercise the power in terms of the Constitution. Consequently, the Public Protector directed the President to establish a commission of inquiry to probe the allegations further. The President argued that the Public Protector had overreached her powers and trespassed upon his powers as Head of State. In the State Capture judgment, the High Court found that the Public Protector’s direction to the President to establish a commission of inquiry was lawful and binding. This article investigates whether the Public Protector may compel the President to establish a commission of inquiry, and whether such an order does not violate the doctrine of the separation of powers. It also probes the nature and extent of the Public Protector’s investigatory powers, vis-à-vis the President’s discretion in appointing a commission of inquiry. The article argues that the President’s power in the process is too broad and should be curtailed to enhance accountability.